2019
DOI: 10.1039/c9an00771g
|View full text |Cite
|
Sign up to set email alerts
|

Profiling embryonic stem cell differentiation by MALDI TOF mass spectrometry: development of a reproducible and robust sample preparation workflow

Abstract: A fast and robust sample preparation method for MALDI TOF MS analysis of whole mammalian cells and phenotypic profiling of mESCs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…phosphate buffered saline, PBS) to remove residual culture medium and additives. PBS has been reported not to interfere with MALDI TOF MS significantly [49]. However, we observed that it may induce random quenching of ionization and decreased intensity of peaks.…”
Section: Intact Cell Maldi Tof Ms Of Hescsmentioning
confidence: 47%
“…phosphate buffered saline, PBS) to remove residual culture medium and additives. PBS has been reported not to interfere with MALDI TOF MS significantly [49]. However, we observed that it may induce random quenching of ionization and decreased intensity of peaks.…”
Section: Intact Cell Maldi Tof Ms Of Hescsmentioning
confidence: 47%
“…Several studies have noted the importance of uniform, homogeneous spots in MALDI–MS assays. [ 10,11,24 ] It is well known that DHB matrix can form inhomogeneous spots, with greatly varying intensities of analyte ions across the spot. This has prompted some authors to stop using it in assays, and others to employ matrix sprayers to prepare samples by spray‐coating rather than dried droplets.…”
Section: Resultsmentioning
confidence: 99%
“…This has prompted some authors to stop using it in assays, and others to employ matrix sprayers to prepare samples by spray‐coating rather than dried droplets. [ 10,11 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of MALDI-TOF-MS in the analysis of metabolites of low molecular weight compounds allows eliminating chromatographic separation [10]. MALDI-MS is widely used for the analysis of large compounds, such as proteins, peptides, and also whole bacteria cells [11][12][13]. Analysis of low molecular weight compounds by MALDI-MS is a current analytical challenge [14].…”
Section: Introductionmentioning
confidence: 99%